Representações sociais de crianças sobre corpo negro e cabelo crespo: relações étnico-raciais na Educação Infantil - Silva, Kátia Karoline Ferreira (2022)
This study sought to reflect on the social representations of children about the phenotypic markers black body and curly hair, making methodological use of Afro-Brazilian children's literature. So it started with the question: what are the social representations of children about the phenotypic markers black body and curly hair from the pedagogical experiences carried out through AfroBrazilian children's literature, during the Covid-19 pandemic.I carried out 7 pedagogical. interventions with books by Kiusam de Oliveira, Lucimar Rosa Dias, Sonia Rosa, Cristiane Sousa, among others, remotely during the Covid-19 pandemic in 2020, with children from a preschool educational center of the Municipal Education Network from Fortaleza/Ceará State. Seven children participated in this research, aged between 5 and 6 years old and the teacher responsible for the class. To achieve the proposed objective and taking into account the limitations imposed by social isolation, I carried out a qualitative research, using collaborative action research to deepen our discussions. As a theoretical basis, in relation to social representations, we read Teles (2010) and Cruzoé (2014); Trinidad (2011), Santiago (2014), Nunes (2016) and Cardoso (2018), which show us new views on the subject in question, in addition to denouncing the racism present in our relationships in society, presenting also the vision that Black and non-black children themselves have of their lives. I also worked with the reflections of Gomes (2002, 2003, 2019, 2020) which helped me reflect upon body and hair as symbols of Black identity. As a result, I noticed that in the words of the children, in this research there is a reproduction of the fallacy of the absence of blacks in Ceará State, revealed by the use of the “moreno” category as a way of whitening Black bodies. They told us about the silences that affect them, showing difficulties in recognizing themselves as Black, as I remarked, for instance, in the absence of colors in the drawings. I also noticed the muting by the audios when their body and hair markers were never highlighted. On the other hand, curly hair was seen, mainly by girls, in a positive way, being always highlighted in their speeches for their details, hairstyles and for the strength present in the representations found in the works used during the experiences built in the virtual space.